Strategic communication of sustainable corporate responsibility practices of Tenaga Nasional Berhad: influence on reputational landscape / Abadan Jasmon - Jasmon, Abadan (2019)
The purpose of this case study is to explore the success of Malaysia’s power industry, Tenaga Nasional Berhad, in aligning communication strategies to improve its reputation, which at one time was deteriorating. The problem statement can be stated as: Even after its privatization in 1990, the Malaysian power industry still exhibits its pre-privatisation period characteristics of operational and cost inefficiencies, and lack of corporate responsibility. Interviews, corporate documents, research articles, website press releases, and other publications, comprised the data. Pursuing a triangulated approach, the following methods were applied: first, qualitatively analysed the contents of corporate documents; second, qualitatively analysed the contents of senior management interview. The application of these methods helped answer the central research question of how appropriately and effective TNB’s communication with its critical stakeholders regarding corporate responsibility.